(untitled) (Faculty of Education Scientific Journal, 2024)
During the months of September and October 2022, a research was carried out in the eastern part of Sirte city to examine various chemical properties of groundwater. This involved assessing the levels of total dissolved solids (TDS), chlorine (Ch), calcium (Ca), total dissolved solids (T.D), magnesium (Mg), ammonium (Nh4), phosphate (po4-3), and carbonate (CO3). The study employed an analytical method to analyze the collected samples and selected ten wells to cover the entire agricultural area within the research location. The findings of the study highlighted the viability of cultivating crop varieties that are resilient to high salinity levels, particularly those of strategic importance. Examples of such crops include palm trees, pomegranate, figs, and olives, as well as winter crops such as barley and cotton. Conversely, it is advisable to refrain from cultivating summer crops. The study made several recommendations, with the most crucial ones being to grow crop types that can tolerate high levels of salt, particularly those that are strategically important. These crops include fruit trees like palm, pomegranate, fig, and olive, as well as cultivating winter crops like barley and cotton exclusively